Lipid production via simultaneous conversion of glucose and xylose by a novel yeast, Cystobasidium iriomotense. - Ayumi Tanimura (PLoS ONE, 2018)
The yeast strains IPM32-16, ISM28-8sT, and IPM46-17, isolated from plant and soil samples from Iriomote Island, Japan, were explored in terms of lipid production during growth in a mixture of glucose and xylose. Phylogenetically, the strains were most closely related to Cystobasidium slooffiae, based on the sequences of the ITS regions and the D1/D2 domain of the LSU rRNA gene. The strains were oleaginous, accumulating lipids to levels > 20% dry cell weight. Moreover, kinetic analysis of the sugar-to-lipid conversion of a 1:1 glucose/xylose mixture showed that the strains consumed the two sugars simultaneously. IPM46-17 attained the highest lipid content (33%), mostly C16 and C18 fatty acids. Thus, the yeasts efficiently converted lignocellulosic sugars to lipids, aiding in biofuel production (which benefits the environment, promotes rural jobs, and strengthens fuel security). The strains constituted a novel species of Cystobasidium, for which we propose the name Cystobasidium iriomotense (type strain ISM28-8sT = JCM 24594T = CBS 15015T).